The role of environmental sustainability as a mediator in the relationship between green accounting and corporate performance in Jordan - Yaser Al Frijat; Mohammad Altawalbeh; Mohammad Al-Hajaia (Problems and Perspectives in Management)
Green accounting is becoming a top issue in global opinion, especially given the environmental and climatic conditions that have become a concern for all countries. The study aims to explore the role of environmental sustainability as a mediator in the relationship between green accounting and corporate performance in Jordan. In the sample of industrial company managers, 259 responses were deemed suitable for in-depth statistical analysis. Smart PLS 4 was employed to analyze sample responses. The structural modeling findings demonstrate a positive association between green accounting and environmental sustainability with a p-value of 0.000, which is significant at the 0.05 level. Path coefficients corroborated the statistically significant positive association between green accounting and company performance, which was significant at the 0.05 level with a p-value of 0.029. The findings also demonstrate an influential correlation between environmental sustainability and company performance with a p-value of 0.000, which is significant at the 0.05 level. The results confirmed that environmental sustainability had an influential mediating influence on the relationship between green accounting and corporate performance with a p-value of 0.000.